New DNA based dynamical S-Box for block cipher - Chng, Chern Wei; Md. Yasin, Sharifah; Abdullah, Mohd. Taufik; Udzir, Nur Izura (International Organization of Scientific Research, 2018)
DNA based technique has grown rapidly among researchers in introducing the latest network security algorithms, which can enhance the strength of the current cryptosystem. DNA-based techniques are able to provide a high degree of cryptography algorithm. This article discusses a new DNA based Dynamical S-Box for the symmetric keys block ciphers. The DNA based Dynamical S-Box is proposed using a polynomial calculation in producing an unknown DNA sequences of {A,C,G,T} in mapping the S-Box table in the form of metric [16x16]. The National Institute of Technology and Technology (NIST) 15 Test is used to verify the cipher for this DNA based Dynamical S-Box. However, S-Box testing criteria have been used to verify the crypto security vulnerabilities by the new DNA based Dynamical S-Box. The simulated end result shows that the proposed DNA based Dynamical S-Box can provide a good level of safety after the NIST Randomness Test shows the value is random.